2019
DOI: 10.6001/biologija.v65i2.4025
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Alnus (Betulaceae) in Iran using molecular ITS markers and morphological characteristics

Abstract: Alnus (Alder) is a genus of Betulaceae, which comprises more than 29 species in the world. According to different classifications of flora, eight taxa of the genus naturally grow in Iran and are distributed along the northern slope of Albourz Mountains in Iran (Hyrcanian forests). In the current research, we investigated morphological characteristics and phylogenetic relationships of 31 populations of the genus in Iran. Twenty-eight qualitative and quantitative traits were studied for morphological evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…According to seed morphological UPGMA tree, three subspecies of A. glutinosa were close together. Similar results were reported by Shayanmehr et al (2014) and Gholamiterojeni et al (2019). They investigated morphological features and phylogenetic relationship using molecular ITS markers of some Alnus taxa and reported that these sub-species had very similar features.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…According to seed morphological UPGMA tree, three subspecies of A. glutinosa were close together. Similar results were reported by Shayanmehr et al (2014) and Gholamiterojeni et al (2019). They investigated morphological features and phylogenetic relationship using molecular ITS markers of some Alnus taxa and reported that these sub-species had very similar features.…”
Section: Discussionsupporting
confidence: 82%
“…The results of investigation revealed the suitability of ultrastructure characteristics such as a micro-morphological structure for solving the taxonomical ambiguities in this genus. In more recent morphological characteristics, both varieties of A. subcordata placed far from each other in different groups (Gholamiterojeni et al, 2019). Quantitative seed morphological characteristics varied among the taxa and could be used as the diagnostic features in taxa identification, as shown by PCA bi-plot.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations